Placental concentrations of alkali metals and their associations with neural tube defects in offspring. (April 2022) - Pi, Xin; Wang, Di; Wang, Chengrong; Li, Zhiwen; Wang, Linlin; Yue, Wentao; Yin, Chenghong; Jin, Lei; Ren, Aiguo
Abstract: Introduction: The role of alkali metals in the development of neural tube defects (NTDs) is little known. We examined the associations between placental concentrations of lithium (Li), sodium (Na), potassium (K), rubidium (Rb), and cesium (Cs), and the occurrence of NTDs in fetuses. Methods: 408 women who had NTD-affected pregnancies and 593 women who delivered healthy infants were included. Logistic regression, weight quantile sum regression (WQSR), and Bayesian kernel machine regression (BKMR) were applied to assess whether these metals are associated with the occurrence of NTDs. Results: Cs showed an inverse association with the odds of NTDs [adjusted odds ratio (aOR): 0.58, 95% confidence interval (CI): 0.36–0.91] in single-metal logistic model. Estimates did not change much in the multiple-metal logistic model. In WQSR, the WQS index was inversely associated with the odds of NTDs (aOR: 0.62, 95%CI: 0.51–0.75), in which Cs (weighted 0.45) had the highest weight. In BKMR, the odds of NTDs decreased with the levels of the five-metal mixtures. Cs was associated with decreased odds of NTDs when the remaining four metals were fixed at their 25 th and 50 th percentiles, while Na was associated with increased odds of NTDs when setting other metals at the 25 th, 50 th, or 75 th percentile. Discussion: A high concentration of Cs and Na in placental tissue was respectively associated with decreased and increased odds of NTDs. In addition, the occurrence of NTDs decreased with the levels of the five-metal mixtures. Graphical abstract: Image 1 Highlights: Five alkali metals in placental tissue were determined. Single and mixture effects of the metals on neural tube defects (NTDs) were examined. A higher Cs concentration was associated with a decreased occurrence of NTDs. A higher Na concentration was associated with an increased occurrence of NTDs. NTD occurrence decreased with the mixture levels of the five alkali metals.